Lives that change lives: the pedagogical practice of an instructor in the SENA, Guaviare Regional - Malagón Ruiz, Rusby Yalile
The SENA is an educational context so broad and diverse that it is easy to meet the humanity of different actors who surprise with their stories, who from their daily practices contribute to the growth of the country and leave on high what it means to be a teacher, an instructor of the SENA. This is the case of instructor Ángela Patricia Rivera, who currently occupies the role of the instructor in the Guaviare regional; it is inevitable not to become joyful with her enthusiastic and positive spirit to read about her regional and the institution in general, as intended in this text.